Australian Communities That Care (CTC) intervention: Benefit-cost analysis of a community-based youth alcohol prevention initiative. - Julie Abimanyi-Ochom; Sithara Wanni Arachchige Dona; Shalika Bohingamu Mudiyanselage; Kanika Mehta; Margaret Kuklinski; Bosco Rowland; John W Toumbourou; Rob Carter (PLoS ONE)
Background Internationally, adolescent alcohol consumption has been a major community concern for decades. Globally, there is a growing array of interventions aimed at preventing youth alcohol-related problems. Notably, the Communities that Care (CTC) process in the USA has proven to be a cost-effective intervention, leading to a reduction in adolescent alcohol-related problems. In Australia, the CTC trial has shown positive outcomes such as reduced adolescent alcohol and drug use, antisocial behaviors, and the availability of alcohol in the community. To encourage wider adoption, it is essential to ascertain the cost-effectiveness of the Australian CTC trial and its potential impact on addressing youth alcohol problems. Method We conducted a limited societal perspective benefit-cost analysis focused on reducing adolescent (aged 10-14) alcohol use in the initial four CTC communities in Australia, spanning 2001 to 2015. To ensure accuracy, estimated benefits were adjusted for joint effects to prevent the double counting of the benefits over time. Results The Australian CTC trial, as an adolescent alcohol prevention strategy, demonstrates robust economic credentials, delivering a return of AUD 2.6 for each dollar invested. The cost savings resulting from the reduction in alcohol consumption were estimated at AUD 123 per youth per 15 years and AUD 8 per person per year. The average cost of the CTC trial amounted to AUD 48 per youth over 15 years and AUD 3 per youth per year. The largest contribution to primary benefits were reductions in crime and violence with 93% of the total benefits. Conclusions This study makes a valuable contribution to the international economic evidence related to youth alcohol prevention initiatives. The results affirm the strong cost-effectiveness potential of the initial CTC trial implementation in Australia. Moreover, conducting further cost-benefit modelling for additional outcomes and beyond the intervention's timeframe is likely to enhance the economic viability of the CTC trial.